2003
DOI: 10.1046/j.1365-2230.2003.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the ARS (component B) gene encoding SLURP-1 in a family with Mal de Meleda

Abstract: Mal de Meleda is a rare, autosomal recessive form of palmoplantar keratoderma. The disease has been mapped to chromosome 8 qter, and recently mutations in the ARS (component B) gene have been identified in families with this disorder. We describe a small family of Turkish origin with Mal de Meleda and identified a novel homozygous mutation, L98P, in ARS (component B). These findings extend the body of evidence implicating mutations in the ARS (component B) gene in Mal de Meleda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…It is located in exon 3 corresponding to the Cterminus of the protein which probably is involved in the protein binding to its receptor [19]. Moreover, the truncated protein formed lacks one of the disulfide bridges which is critical for the normal function of the protein [22]. This mutation has been previously reported in patients from Turkey and Croatia [13].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is located in exon 3 corresponding to the Cterminus of the protein which probably is involved in the protein binding to its receptor [19]. Moreover, the truncated protein formed lacks one of the disulfide bridges which is critical for the normal function of the protein [22]. This mutation has been previously reported in patients from Turkey and Croatia [13].…”
Section: Discussionmentioning
confidence: 83%
“…In fact, most mutations are clustered in exon 3. MDM is an autosomal recessive palmoplantar keratoderma that is clinically and genetically heterogeneous [2] and detailed genotype-phenotype correlations are as yet unclear [22]. Most of the patients are members of consanguineous families [1].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Leu-135 is conserved across mammalian species. Moreover, the corresponding residue in SLURP1, CD59, and UPAR is also a leucine, and a missense mutation involving that leucine in SLURP1 causes mal de Meleda (21).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al suggest it may, if only for historical reasons [37]. Figure 2 [7,11,17,[32][33][34][35][36][38][39][40][41] shows an exon/intron map of the SLURP-1 gene and lists the mutation types and their location in Mal de Meleda (as well as the Gamborg-Nielsen variant).…”
Section: Genetics and Pathophysiologymentioning
confidence: 99%
“…c.1A>C (p. Met1Leu) [34] Ivs1+1G>A (alt splice site) [17] c.82delT (p.Cys28fs32X) [33] Ivs2+1G>A (alt splice site) [33] c.229T>C (p.Cys77Arg) [35] c.43T>C (p.Trp15Arg) [36] c.58+5G>T (alt splice site) [11] c.129C>A (p.C43X) [38] c.244C>T (p.Pro82Ser) [32] c.212G>A (p.Arg71His) [41] c.256G>C (p.Gly86Arg) [34] c.212G>C (p.Arg71Pro) [36] c.256G>A (p.Gly86Arg) [34] c.280T>A (p.Cys94Ser) [7] c.286C>T (p.Arg96Term) [33] c.293T>C (p.Leu98Pro) [39] c.296G>A (p.Cys99Tyr) [40] AD autosomal dominant, AR autosomal recessive, PPK palmoplantar keratoderma Reed et al [73] discussed effective treatment with oral 13-cis retinoid acid following failed treatment with corticosteroid, lactic acid, retinoid acid, and emollients. More recently, Gruber et al [32] showed effective treatment with oral acitretin 20 mg/day plus topical antimicrobial and keratolytic therapy.…”
Section: Intron 1 (405 Bp) Intron 2 (526 Bp)mentioning
confidence: 99%